2003
DOI: 10.1128/aem.69.7.3986-3995.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bacillus methanolicus Citrate Synthase II Gene, citY , in Regulating the Secretion of Glutamate in l -Lysine-Secreting Mutants

Abstract: The unusual metabolic properties of aerobic, restrictive, thermotolerant methylotrophic bacteria make them useful for the production of recombinant proteins, vitamins, amino acids, coenzymes, and cytochromes (12). Bacillus methanolicus MGA3 (ATCC 53907) is a gram-positive bacterium with a growth optimum of 50°C to 53°C. Cell extracts of this bacterium grown on methanol contain an NAD-dependent methanol dehydrogenase (3, 13), have 3-hexulose-6-phosphate synthase, fructose bisphosphate aldolase, and transaldolas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
69
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 52 publications
5
69
0
1
Order By: Relevance
“…B. methanolicus cells growing exponentially (OD 600 ϭ 1.0) in defined media were harvested and washed twice in ice-cold potassium phosphate buffer (50 mM; pH 7.6). The cells were disrupted by sonication as previously described (7). Coupled HPS-PHI activities were assayed by monitoring the fixation of formaldehyde with ribulose-5-phosphate (28).…”
Section: Methodsmentioning
confidence: 99%
“…B. methanolicus cells growing exponentially (OD 600 ϭ 1.0) in defined media were harvested and washed twice in ice-cold potassium phosphate buffer (50 mM; pH 7.6). The cells were disrupted by sonication as previously described (7). Coupled HPS-PHI activities were assayed by monitoring the fixation of formaldehyde with ribulose-5-phosphate (28).…”
Section: Methodsmentioning
confidence: 99%
“…Late-exponential-phase cell cultures were harvested by centrifugation (Sorvall GSA rotor; 4.500 rpm, 10 min, 4°C) and washed twice in 50 mM potassium phosphate buffer (pH 7.5) containing 5 mM MgSO 4 6-bisphosphatase (and sedoheptulose-1,7-bisphosphatase) gene; rpi, ribose-5-phosphate isomerase gene; rpe, RPE gene; H-6-P, hexulose 6-phosphate; F-1,6-dP, fructose 1,6-bisphosphate; GAP, glyceraldehyde 3-phosphate; DHAP, dihydroxyacetone phosphate; X-5-P, xylulose 5-phosphate; E-4-P, erythrose 4-phosphate; S-1,7-dP, sedoheptulose 1,7-bisphosphate; S-7-P, sedoheptulose 7-phosphate, Ri-5-P, ribose 5-phosphate. Sonifer 250) as described previously (11). B. methanolicus cells were incubated at 37°C for 60 min in the presence of lysozyme (5 mg/ml) and 25 U of mutanolysin (10 U/ml; Sigma) before sonication.…”
Section: Methodsmentioning
confidence: 99%
“…For preparation of crude extracts B. methanolicus strains were grown in SOB containing 0.25 M sucrose, and methanol was added at a concentration of 150 mM 1 h prior to harvest to induce MDH expression. For all other purposes B. methanolicus cells were grown at 50°C in methanol minimal vitamin medium (MVcMY medium) containing 1 mM MgSO 4 , high-salt buffer, vitamins, 0.025% yeast extract (Difco), 200 mM methanol, and trace metals essentially as described previously (11). Mannitol medium was MVcMY medium without methanol supplemented with D-mannitol (10 g/liter; Sigma) as the sole carbon source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We later showed that this organism has two different HD-encoding genes, hom-1 and hom-2, and that the classical hom-1 mutant B. methanolicus strain M168-20 had 60-fold increased L-lysine production (6). Interestingly, intracellular metabolite analysis and manipulations with pyruvate carboxylase and citrate synthase indicated that the oxaloacetate precursor supply is not a major bottleneck for L-lysine overproduction in B. methanolicus (4,6).…”
mentioning
confidence: 99%